MANAGEMENT OF SEVERE UPPER AIRWAY OBSTRUCTION IN INFECTIOUS MONONUCLEOSIS: EMERGENT ADENOTONSILLECTOMY - (:unkn) unknown (My University, 2016)
Infective mononucleosis (IM) is a viral diseaseaffecting a wide range of organ system especially inthe head and neck region. Usual manifestation of IM isacute acute pharyngotonsillitis, fever andlymphadenopathy. In some patients adenotonsillartissue is so severe affected that can compromise theairways. We present a case of a 5-year-old girl with IMaccompanied by upper airway obstruction symptomsof stridor and difficult breathing. Results The patientwas diagnosed as IM with severe upper airwayobstruction. Initial steroid treatment resulted noclinical response. Therefore, hot adenotonsillectomywas performed. Hot adenotonsillectomy can be lifesaving and have dramatic benefits especially in patients with severe upper airway obstruction as acomplication of IM.

Enfeksiyöz mononükleoz (EMN) çoğunlukla EbsteinBarr virüsünün (EBV) neden olduğu, sıklıkla akut adenotonsillit, ateş ve lenfadenopatinin eşlik ettiği yaygın sistemik bir enfeksiyondur. Hastalığın hematolojik, hepatik, solunumsal ve psikolojik komplikasyonları en sık görülen komplikasyonları olup üst hava yolu obstruksiyonu ciddi komplikasyondur ve fatal seyredebilir. Bu sunuda EBV adenotonsillit enfeksiyonu sonrası üst hava yolu obstruksiyonuna bağlı solunum sıksıntısı gelişen, acil adenotonsillektomi operasyonu yapılan bir olgu sunulacaktır.
ACİL ADENOTONSİLLEKTOMİ: EBV’YE BAĞLI ILERI DERECE ÜST HAVA YOLU OBSTRÜKSİYONU
Keywords: Kulak, Burun, Boğaz